2022
DOI: 10.1101/2022.04.19.488749
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wolbachiainhibits ovarian formation and increases blood feeding rate in femaleAedes aegypti

Abstract: Wolbachia, a gram-negative endosymbiotic bacterium widespread in arthropods, is well-known for changing the reproduction of its host in ways that increase its rate of spread, but there are also costs to hosts that can reduce this. Here we investigated a novel reproductive alteration of Wolbachia wAlbB on its host Aedes aegypti, based on studies of mosquito life history traits, ovarian dissections and gene expression assays. We found that an extended period of the larval stage as well as the egg stage as previo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 83 publications
(121 reference statements)
2
3
0
Order By: Relevance
“…This effect was Wolbachia-specific because uninfected females stored for the same amount of time never became infertile. The effects of egg storage on infertility are similar to those described previously for the wAlbB infection (Lau et al, 2021a(Lau et al, , 2022 but substantially weaker, with 50% infertility observed after only 9 weeks for wAlbB. The weakening of cytoplasmic incompatibility is likely due to partial or complete loss of Wolbachia during egg quiescence as demonstrated previously for wMel (Lau et al, 2021a).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This effect was Wolbachia-specific because uninfected females stored for the same amount of time never became infertile. The effects of egg storage on infertility are similar to those described previously for the wAlbB infection (Lau et al, 2021a(Lau et al, , 2022 but substantially weaker, with 50% infertility observed after only 9 weeks for wAlbB. The weakening of cytoplasmic incompatibility is likely due to partial or complete loss of Wolbachia during egg quiescence as demonstrated previously for wMel (Lau et al, 2021a).…”
Section: Discussionsupporting
confidence: 85%
“…We showed previously that the wAlbB Wolbachia strain causes female mosquitoes to become infertile if they hatch from stored eggs (Lau et al, 2021a(Lau et al, , 2022. We scored the proportion of females used in crosses in Figure 4 that laid eggs as a measure of infertility, although we note that the storage period to induce this effect is much longer than described previously for wAlbB (Lau et al, 2021a).…”
Section: Wmel-infected Females Hatching From Longterm Stored Eggs Bec...mentioning
confidence: 91%
See 1 more Smart Citation
“…This effect was Wolbachia-specific because uninfected females stored for the same amount of time never became infertile. The effects of egg storage on infertility are similar to those described previously for the wAlbB infection [13,35] but substantially weaker, with ~50% infertility observed after only nine weeks for wAlbB. While the additional costs of wMel infection were only apparent after long-term storage, interactions with other environmental factors such as high temperatures, which also reduce cytoplasmic incompatibility by wMel [44], could exacerbate these costs.…”
Section: Discussionsupporting
confidence: 76%
“…We showed previously that the w AlbB Wolbachia strain causes female mosquitoes to become infertile if they hatch from stored eggs [13, 35]. We scored the proportion of females used in crosses in Figure 4 that laid eggs as a measure of infertility, although we note that the storage period to induce this effect is much longer than described previously for wA lbB [13].…”
Section: Resultsmentioning
confidence: 94%